Last call [compact disc, abridged] : the rise and fall of Prohibition - Okrent, Daniel, 1948- (Simon & Schuster Audio, 2010)
Okrent explores the origins, implementation, and failure of that great American delusion known as Prohibition. "Last Call" explains how Prohibition happened, what life under it was like, and what it did to the country.